La fiscalidad de Castellón entre 1833 y 1840: las contribuciones reales y municipales - Aguilera López, José (Millars. Espai i Història, 2018)
Sketch on the contribution of the city of Castellón to the Royal Treasury between 1833 and 1840. Study of the collections known as "contribuciones reales y municipales con sus agregados", by accomplishing an exploration Qn the wealth of the city, the fiscal pressure, the distribution of the income, the contributors, goods Qn the those which are aggravated by these contributions, etc. that permit to establish a global balance on the taxes of that period of time and to diagnose the impact that the bourgeois revolution will have some years later on the fiscal reform of Mont-Santillán.